(untitled) (International conference on multidisciplinary science, 2023)
In this article it is explained about the Latin 1st declension nouns that considered as group of nouns that follow a specific pattern of inflection. The authors analyze nouns that are typically feminine and nominative singular form. Nouns are declined to indicate their grammatical function in a sentence, such as whether they are the subject, object, or possessive.